Análise Discursiva: As ideologias presentes nas interações de monitoras em oficinas investigativas de física - Rodrigues, Nathalie Akie Omachi (2021)
Physics, in elementary school, can be conducted through investigative activities that encourage students to find and solve small problems and that lead them to argue. In this perspective, there are studies on Teaching by Research (EI), that contributes to a reflection on the processes of making and teaching science at school. In this context, it is essential the position of the teacher as a mediator, since, if questions do not arouse the interest and reflection of the students, the discussion may become a monologue. From this perspective, we consider that the ideologies and experiences of the teacher will influence his speech and, consequently, in promoting (or not) the argumentation in the classroom, because the word is an ideological product. Thus, this research sought to investigate how the ideologies of a group of monitors, who worked on an extension project of Science for children, enabled argumentative moments during a set of four workshops. To achieve the objectives, investigative workshops were implemented with children and the use of toys in the children's "WITHCHEMISTRY" laboratory, in the Core Science Teaching Institute of Toledo, Parana, Brazil. For data analysis, were considered the assumptions of the discursive analysis in Bakhtin and taken into account the questions submitted by this author to: genre of speech, ideology, word and polyphony. The results indicate that the ideologies formed by the monitors leave discursive marks in their interactions with the students, especially when the monitors have experience with IS and understand the meaning of argumentation in didactic activities. These factors were determinant to promote the argumentation of students, while the monitors who did not understand what argumentation was had greater difficulty in conduct the workshops.